Pathology of Regional Development Management in Khuzestan Province - Reza Kayednejad; Hamid Pishgah hadian; Gholamhoseyn Bolandian; Dravishpour Hojjatollah (توسعه اجتماعی, 2022)
Khuzestan,despite its high potential for development,has problems in regional development for various reasons.This study seeks the pathology of this issue by assessing the opinion of the instrumental and intellectual elites of the province.To finally be able to reach the perspective of the pathology of regional development management in Khuzestan province.In this research, using a survey method,20questions were asked from 61 instrumental and intellectual elites of the province.The main question of this research is what are the most important harms of regional development management in Khuzestan province? Findings show that 6 cases of "non-employment and use of specialized and efficient forces", "priority of political issues over regional development policies", "lack of capacity building in various social, economic and productive areas", "disregard for conditions "Economic, political, social", "inconsistency between national divisions and regional management system" and "dependence of regional institutions on extra-regional government resources" are the main harms of regional development management in Khuzestan province. In other words, among different dimensions, human factors (expert force), institutional factors, socio-economic factors and regional factors have the greatest impact on the lack of development of the region.